PAKKADES.ID UNTUK MENDUKUNG PHYSICAL DISTANCING SAAT MUSYAWARAH ANGGARAN PEMBANGUNAN DESA SEBAGAI UPAYA MENGHADAPI PANDEMI - Trias Bratakusuma (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Nowadays, although the pageraji village government has implemented e-government but more to increase services through the elimination of the old and complicated bureaukasi structure. In this case more information systems are used to speed up and automate processes. There is no information system yet focused on supporting the decision process. Pakkades.id is a type of information system intended to facilitate budgeting mechanisms. In the process of drafting village development budgets, community participation or aspirations are urgently needed. However, there are often obstacles to getting aspirations from the community because the mechanism that is implemented now only through deliberations implemented one day, this will narrow the reach. Therefore, with the implementation of Pakkades.id which is the result of the study authors of the Funding Ristek Dikti 2019 is expected to efficiency and effectively process decision making through the process of capturing the aspirations of the community better.